Microbial respiration and nitrogen mineralization in soil amended with different proportions of vermicompost and coir dust (Bangladesh Journal of Agricultural Research, 2010)
The effect of different combinations of vermicompost and coir dust on microbial respiration and nitrogen mineralization in soil was studied under laboratory conditions. Treatment with 75% vermicompost and 25% coir dust (T2) demonstrated the highest carbon mineralization and NH+4-N contents followed by treatment T1 (100% vermicompost) and T3 (50% vermicompost and 50% coir dust). Despite the varied NO3-N contents at the initial stages of incubation, the NO3-N content steadily increased for all the treatments at day 49 onwards. The highest NO3-N content was observed in T1 followed by that in T2 and T3. Such studies need be conducted under field conditions to reach a definite conclusion. Key Words: Vermicompost; coir dust; mineralization. DOI: 10.3329/bjar.v34i4.5830Bangladesh J. Agril. Res. 34(4) : 537-543, December 2009